The Impact of Political Connection, Corporate Social Responsibility Disclosure, and Woman Director on Tax Avoidance - Rusli; Simatupang, Ravella Elsa Gressa; Vince Ratnawati; Ria Nelly Sari (JAS (Jurnal Akuntansi Syariah), 2025)
This test pursuit to empirically observe the impact of Political Connection, Corporate Social Disclosure, and Woman Director on Tax Avoidance (Empirical observe of manufacturing corporations indexed on the Indonesia Stock Change for the 2021-2023 length). The populace of this examine includes all manufacturing corporations indexed on the Indonesia Stock Change for the length 2021-2023, namely 270 corporations. The sample of this look at amounted to seventy six corporations studied for three years, so that the overall sample turned into 228. The sampling used on this have a look at used a purposive sampling method, at the same time as the facts processing method used on this have a look at was panel data regression with manage variables of company size, sales growth, and Leverage the use of STATA software version 17. The effects of this observe imply that Political Connection haven't any effect on Tax Avoidance, Corporate Social responsibility Disclosure has a negative impact on Tax Avoidance, and Woman Director has a negatif impact on Tax Avoidance. This studies is the usage of tax avoidance proxies using permanently recorded tax variations (DTAX), due to the fact it's miles taken into consideration extra able to discover tax avoidance in terms of efforts to reduce taxable income and is superior to other measurements, such as the overall effective tax fee (ETR) and CETR.